PENGARUH FASILITAS E-BILLING DAN E-FILING TERHADAP KEPATUHAN WAJIB PAJAK DI KOTA BATAM - Nita, Elvira; Efriyenti, Dian (SCIENTIA JOURNAL, 2021)
The difficulty of filling the tax report, lack of knowledge about tax reporting procedure, E-Billing, and E-Filling lead to less taxpayer compliance in pay and report their tax. Therefore, the government improves tax services and creates E-Billing and E-Filing features that can help taxpayers. The purpose of this study aimed to examine the effect of E-Billing and E-Filing facilities on the taxpayer compliance in Batam City. The population in this study were 43.763 individual taxpayers that already registered in Kantor Pelayanan Pajak (KPP) Batam Selatan which submit their tax report through E-Filing. The sample of this study were 100 respondents that taken using slovin formula. This study were using incidental sampling technique. Data obtained by questionnaire, measured by a likert scale and proceed by SPSS Porgram. The result of this study showed that E-Billing facility (X1) has a significant effect on individual taxpayers compliance with significant value 0,000 < 0,05. E-Filing Facility (X2) also has a significant effect on individual taxpayers compliance with significant value 0,002 < 0,05. Both E-Billing (X1) and E-Filing facilities (X2) have a significant effect on individual taxpayers compliance which already registered in Kantor Pelayanan Pajak (KPP) Batam Selatan.